An Integrated Bridgeless PWM Based Power Converter for Power Factor Correction - Akhila, K. R.; Pradeep, Selva (Asian Journal of Science and Applied Technology, 2014)
This paper proposes a new integrated bridgeless PWM based power converter for power factor correction. The proposed converter integrates the bridgeless boost rectifier with the asymmetrical pulse-width modulation half-bridge dc–dc converter. The proposed converter provides an isolated dc output voltage without using any full-bridge diode rectifier. Conduction losses are lowered by eliminating the full-bridge diode rectifier. Zero-voltage switching of the power switches reduces the switching power losses. The proposed converter provides high power factor and direct power conversion from the line voltage to an isolated dc output voltage without using the full bridge diode rectifier and also gives a high efficiency, and low cost. Conduction losses are lowered with a simple circuit structure.